AGE AND GENDER-WISE OCCURRENCE OF PSEUDOMONAS AERUGINOSA IN MINGORA, SWAT, AND THE EFFECTIVENESS OF COMMONLY USED ANTIBIOTICS FOR ITS TREATMENT (Journal of Medical & Health Sciences Review, 2025)
Pseudomonas aeruginosa is a gram-negative, aerobic, non-spore-forming rod that causes various infections in both immunocompetent and immunocompromised hosts. It is commonly found in the environment and is an opportunistic pathogen in hospital settings. Its unique ability to form biofilms increases antibiotic resistance and resists host defenses. Pseudomonal infections can occur in various parts of the body. It is the second most common cause of nosocomial pneumonia, urinary tract infection, surgical- site infection, and fifth most common isolate overall. Pseudomonal infections are increasingly resistant to certain antibiotics and a 2-drug regimen is recommended for severe sepsis, septicemia and inpatient neutropenia. This study aims to investigate the age- and gender-wise occurrence of P. aeruginosa in Mingora, Swat, KP, and evaluate the effectiveness of commonly used antibiotics in its treatment. The obtained results revealed the highest occurrence rate of 40 % in age group 18-30 years, followed by 34% in the age group of 32-42 years and 26% in elders of 41-52 years’ age. Regarding the gender distribution, the occurrence rates of 58% and 42% were observed in males and                      females respectively. The antimicrobial susceptibility results showed Ciprofloxacin as                   the most effective antibiotic against P. aeruginosa isolates. The rates of susceptible isolates were ciprofloxacin (CIP) 72%, amikacin (AK) 70%, ceftazidime (CAZ) 63%, imipenem (IPM) 52%, piperacillin/tazobactam (TZP) 50%, cefepime (FEP) 46%, aztreonam (ATM) 45%, tobramycin (TOB) 42% and levofloxacin (LEV) 33%. 58% of  isolates were resistant to more than two groups of antibiotics and were regarded as multidrug resistant (MDR).